Are Pakistan's Women Entrepreneurs Being Served by the Microfinance Sector? - Safavian, Mehnaz; Haq, Aban (Washington, DC: World Bank, 2013)
Fostering the entrepreneurship of women is important for Pakistan's economic growth and inclusion agenda, and access to financial services is an important component of starting and growing a business for women entrepreneurs. Most women?owned businesses are small, household?based cottage industries; microfinance products should be a natural source of start?up and working capital finance for this clientele. Microfinance portfolio data suggest that although Pakistan's sector has shown improvement in reaching women, it still lags its regional peers, only 59 percent of microfinance clients are women. The original purpose of this work was to determine whether women entrepreneurs have access to, and are using, microfinance loans as a source of finance for their businesses. However, the findings of the report go beyond the narrow objective of understanding whether microfinance institutions (MFIs) are reaching Pakistan's businesswomen. As the research unfolded, the evidence suggested that not only are women entrepreneurs not being served, but also that the outreach to women in general is potentially more limited than previously assumed and that the issues of consumer protection and responsible lending practices in Pakistan might merit further exploration. The report raises and addresses two distinct issues. First, some evidence suggests that women are often not the final users of loans, but rather are conduits to male household members. The report documents findings that suggest that the practice of passing on loans to male household members is potentially quite widespread; women may be bearing all the transaction costs and risks of accessing loans, but are not the final beneficiaries. Second, a very low proportion of female microfinance clients are entrepreneurs. The report explores why businesswomen in Pakistan may not be using microfinance products to meet their startup and working capital requirements, in spite of identifying access to finance as a key constraint to their business operations. The report focuses on products, services, policies, and other elements of the business model of microfinance in Pakistan that affect both demand for and access to microfinance by women borrowers, some of whom fall into the narrower category of entrepreneurs.